EFFICACY OF SEVELAMER CARBONATE IN COMBINATION WITH EDIBLE SOURCES IN HYPERPHOSPHATEMIA CONDITION ASSOCIATED WITH CHRONIC KIDNEY DISORDER - P., SHLINI; ROY, DIKSHA; SINGH, RICHA (International Journal of Current Pharmaceutical Research, 2021)
Objective: The main objective of the study was to discover a suitable dietary source of plant origin which can be recommended alongside the medication in case of hyperphosphatemia. Methods: The 2 plant samples chow chow (Sechiumedule) and bitter gourd (Momordica carantia) and two seed samples-Flax seeds (Linumusitatissimum) and Chia seeds (Salvia hispanica) were selected for the study. The samples were extracted using methanol. The filtrate obtained was used for dialysis studies under different conditions. Inorganic phosphate was estimated in each of the conditions. Results: The study indicated perturbation in the absorption of phosphate with the selected plant samples as talked about in the following study. The extreme concentration of phosphate among the four diverse picked plant sources was seen in bitter gourd, which was found to be 0.4686 µmoles/ml. A minimal measure of 0.0693 µmoles/ml of phosphate was found in chia seeds. Chow chow ended up being the best one in hyperphosphatemia condition as the amount of phosphate removed by it along with the drug, sevelamer carbonate, was calculated to be the maximum (0.0561 µmoles). It was followed by chia seeds (0.0429 µmoles) and flax seeds (0.0420 µmoles). Conclusion: The present study concentrates on the impact of various samples of plant extraction that can act on the phosphate absorption in the intestine by the procedure of dialysis.